On the Best Settings to Calculate Ionospheric Irregularity Indices From the In Situ Plasma Parameters of CSES-01 - Michael Pezzopane; Alessio Pignalberi; Paola De Michelis; Giuseppe Consolini; Igino Coco; Fabio Giannattasio; Roberta Tozzi; Simona Zoffoli (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
Electron density (Ne) and temperature (Te) values recorded by the Langmuir probe onboard the first satellite of the China Seismo-Electromagnetic Satellite (CSES-01) mission allow calculating quantities such as the rate of change of electron density index (RODI) and the rate of change of electron temperature index (ROTEI), which are essential to describe the ionospheric irregularities and their dynamics. These two indices depend significantly on two parameters, i.e., the measurement sampling time and the width of the sliding windows used for their computation. Ne and Te measurements from CSES-01 present two different sampling times, i.e., 3 s in the survey mode and 1.5 s in the burst mode. The purpose of this article is to understand what are the best values of these two parameters to be used when computing RODI and ROTEI based on CSES-01 data. The main results of the study show the following: The shorter the data sampling time, the higher the values of the calculated ionospheric indices, which means that it is not possible to merge values of either RODI or ROTEI calculated with a different sampling time; the wider the sliding window used to calculate the indices, the higher the indices. A reasonable compromise between the data sampling time and the satellite orbital velocity suggests that the optimal way to calculate RODI and ROTEI from CSES-01 should be done by considering data with a 3-s sampling time (i.e., in the survey mode or in the downsampled burst mode), and a 24-s wide sliding window.